34y+13=56

Combine 34 and y.

3y4+13=56

Subtract 13 from both sides of the equation.

3y4=56-13

To write -13 as a fraction with a common denominator, multiply by 22.

3y4=56-13⋅22

Write each expression with a common denominator of 6, by multiplying each by an appropriate factor of 1.

Multiply 13 and 22.

3y4=56-23⋅2

Multiply 3 by 2.

3y4=56-26

3y4=56-26

Combine the numerators over the common denominator.

3y4=5-26

Subtract 2 from 5.

3y4=36

Cancel the common factor of 3 and 6.

Factor 3 out of 3.

3y4=3(1)6

Cancel the common factors.

Factor 3 out of 6.

3y4=3⋅13⋅2

Cancel the common factor.

3y4=3⋅13⋅2

Rewrite the expression.

3y4=12

3y4=12

3y4=12

3y4=12

Multiply both sides of the equation by 43.

43⋅3y4=43⋅12

Simplify 43⋅3y4.

Cancel the common factor of 4.

Cancel the common factor.

43⋅3y4=43⋅12

Rewrite the expression.

13⋅(3y)=43⋅12

13⋅(3y)=43⋅12

Cancel the common factor of 3.

Factor 3 out of 3y.

13⋅(3(y))=43⋅12

Cancel the common factor.

13⋅(3y)=43⋅12

Rewrite the expression.

y=43⋅12

y=43⋅12

y=43⋅12

Cancel the common factor of 2.

Factor 2 out of 4.

y=2(2)3⋅12

Cancel the common factor.

y=2⋅23⋅12

Rewrite the expression.

y=23

y=23

y=23

The result can be shown in multiple forms.

Exact Form:

y=23

Decimal Form:

y=0.6‾

Solve for y 3/4y+1/3=5/6